Management of Hemophilia: A Dental consideration - Mukul, Sailesh; Agrawal, Amit (Journal of Orofacial Research, 2018)
Hemophilia is a medical condition that can cause medical emergency for dentist. Hemophilia patients have high risk of bleeding during various dental procedures. Management of bleeding in these patients during & after surgery is the biggest challenge for dental surgeons. Here we present a review on management of hemophilia in dentistry for which literature obtained from published articles, books and manual.